MRI During Spinal Loading Reveals Intervertebral Disc Behavior Corresponding to Discogram Findings of Annular Fissures and Pain Provocation. Issue 22 (15th November 2020) - Torén, Leif; Lagerstrand, Kerstin; Waldenberg, Christian; Brisby, Helena; Hebelka, Hanna
Abstract : Study Design: Retrospective analysis of prospectively collected data. Objective: The aim of this study was to investigate whether spinal loading, depicted with magnetic resonance imaging (MRI), induces regional intervertebral disc (IVD) differences associated with presence and width of annular fissure and induced pain at discography. Summary of Background Data: Annular fissures play a role in low back pain (LBP) but cannot be accurately characterized with conventional MRI. Recently, annular fissures were suggested to influence different load-induced IVD behavior during MRI when comparing LBP-patients and controls. Thus, the loading effect could characterize behavior related to annular fissures noninvasively with MRI. Methods: Lumbar spines of 30 LBP-patients were investigated with MRI with and without loading, discography and CT. Five IVD regions were outlined on sagittal MRI images. Difference in normalized signal intensity (SI) with and without loading was calculated for each region. Eighty-three CT-discograms were graded regarding presence and width of fissures. Discograms were classified as pain-positive if a concordant pain response was obtained at a pressure <50 psi. Results: Comparing IVDs with outer fissures with IVDs without fissures, loading induced different behavior in the two ventral regions and in the posterior region. Higher SI increase in the central region was induced in IVDs with narrower fissures compared to IVDs with wider fissures. In the group of pain-negative discograms, a SI decrease was induced in the dorsal region whereas lack of such in the pain-positive group. Conclusion: The spinal loading-effect, depicted with MRI, reveals different regional behaviors between IVDs with outer fissures compared to those without, and between IVDs with narrow and broad fissures, as well as within posterior annulus between pain-positive and pain-negative discograms. Findings are of importance for future attempts to uncover phenotypes of painful IVDs. Level of Evidence: 2 Abstract : Spinal loading, depicted with MRI, induces different regional alterations between groups of IVDs depending on presence and with of annular fissures. Additionally, loading induces different alterations within posterior annulus between pain-positive and pain-negative discograms. Findings are of importance for future attempts to uncover phenotypes of painful IVDs.